The Ecological Value of Typical Agricultural Products: An Emergy-Based Life-Cycle Assessment Framework - Wang, Yongyang; Liu, Gengyuan; Cai, Yanpeng; Giannetti, Biagio F.; Agostinho, Feni; Almeida, Cecilia M. V. B.; Casazza, Marco (Frontiers in Environmental Science, 2022)
Agriculture, one of the largest ecological-engineered systems, is key to human survival. The realization of its products impacts on food security, ecosystems protection and crucial strategic deployment. With this respect, the monetary value of agri-products should be paralleled with a non-monetary assessment of ecological value for humans. This study, integrating emergy accounting and Life Cycle Costing, sets up an emergy-based life-cycle costing (Em-LCC) framework. Ecosystem services (ES) and dis-services (EDS) are quantified, being delivered together with agricultural products, needed for food provision. EDS, seen as impacts, cover different categories, not completely covered by LCA. Then, the efficiency of products is quantified in two different ways. One is the quantification of the ratio between renewable and non-renewable inputs, assessing the dependency of agricultural productions on non-renewable resources, generating higher impacts on the environment. In parallel, the eco-efficiency is assessed comparing the product cost, based on LCC, with respect to the different EDS, seen as impacts, generated during the production process. The study is applied to six typical Chinese crops, exploring the agricultural eco-product value implementation path. The results showed the agriculture system mainly depends on non-renewable resources. EDS generated by China’s agri-products are higher than the ES produced by them. The Net Ecosystem Service Value (NESV) is mainly concentrated in the North China area. Nevertheless, there is a low correlation between the current price of agri-products and their greenness. Instead, the economic value presents a rising trend with agri-products greenness increasing. Further to discuss effective approaches to sustainable agriculture, it can be seen that, 1) Sustainable agriculture will lead to increased greenness, but it is impossible to improve greenness indefinitely. 2) Improving greenness is an effective way to implement ecological value, another way to preserve and raise ecological value is that reducing the EDS generation. All of these are beneficial to realize agricultural ecological value 3) Reducing in energy consumption leads to EDS decreased but it is not an appropriate way to achieve sustainable development. These findings can provide meaningful suggestions for decision-makers to realize the agri-products ecological value and high-quality development.